The effect of intravenous ascorbic acid in hemodialysis patients with normoferritinemic anemia - Dae Woong Kang; Chi Yong Ahn; Bong Kwan Ryu; Byung Chul Shin; Jong Hoon Chung; Hyun Lee Kim (Kidney Research and Clinical Practice, 2012)
Background: Hemodialysis (HD) patients with functional iron deficiency often develop resistance to recombinant human erythropoietin (rhEPO). Recent studies have shown that intravenous ascorbic acid (IVAA) administration could override rhEPO resistance in HD patients. This study was undertaken to test the effects of IVAA in HD patients with normoferritinemic functional iron deficiency accompanied by EPO-hyporesponsive anemia. Methods: Fifty-eight HD patients with normoferritinemic anemia (between 100 and 500 μg/L) were included and divided into the control (N=25) and IVAA (N=33) groups. IVAA patients received 500 mg of IVAA with each dialysis session for 3 months and an additional 4-month follow-up after the end of the therapy. Results: Twenty patients had a response to IVAA with a significant increase in hemoglobin level (Hgb>1.0 g/dL) and reduction of weekly rhEPO dosage compared with the control group after 3 months of treatment (P<0.05). Compared with non-responders, transferrin saturation (TSAT) was significantly decreased in the responders group (26±11 vs. 35±14%, P<0.05) on baseline data. There was a significant increase in serum iron and TSAT (baseline vs. 3 months, serum iron 57±22 vs. 108±22 μg/dL, TSAT 26±11 vs. 52±7%, P<0.05) and a decrease in serum ferritin (377±146 vs. 233±145 ng/mL, P<0.05) in the responders group (N=20), but no significant changes in the control and non-responders groups (N=13) at 3-month treatment. Conclusion: IVAA can be a potent and effective adjuvant therapy for HD patients with rhEPO-resistant normoferritinemic anemia. In addition, IVAA can reduce the dosage of rhEPO for anemia correction.